The Effect of Work-Family Conflict on Business Sustainability in Micro and Small Enterprises in Bamenda: The Case of Copreneurs’ Businesses - Forsuh, Lesley; Saidou , Baba Oumar; Nyobe, Joseph Magloire (Society & Sustainability, 2025)
This study investigates the effect of work-family conflict on business sustainability in husband-wife (Copreneurs) owned micro and small enterprises in Bamenda, Cameroon. The study utilized a mixed methods research design, incorporating both quantitative and qualitative approaches. The study used a causal research design to test for causality. The quantitative research component involves collecting numerical data through surveys or questionnaires administered to a sample of Copreneurs. The target population of this study was selected businesses that are co-managed by both spouses in Bamenda city, and a sample of 330 Copreneurs was obtained through stratified random sampling. Data was analyzed using ordinary least squares analysis. The analysis reveals a positive relationship between the overall work-family conflict index and business sustainability. However, this relationship is statistically insignificant. Specifically, a unit increase in the work-family conflict index correlates with a 0.11-point increase in business sustainability. In contrast, the work time commitment has a significant negative effect on sustainability, with a coefficient of -0.412, indicating that an increase in work time commitment by Copreneurs leads to a 0.41-point decrease in sustainability. Conversely, role overload demonstrates a significant positive relationship with business sustainability, where a one-point increase in role overload results in a 0.745-point enhancement in sustainability. The study implies that business leaders should acknowledge the dual nature of work-family conflict and its components. Organizations should implement policies that promote work-life balance, such as flexible work schedules and family-friendly practices, to mitigate the negative effects of Work Time Commitment on sustainability initiatives. Training programs focused on time management and prioritization could also equip employees with the skills to balance work demands and sustainability goals effectively.